The Effect of Career Development and Emotional Intelligence on Organizational Citizenship Behavior Mediated by Job Satisfaction in Employees of Drinking Water Companies in Lingga District - Muhammad Yusuf; Anoesyirwan Moein; Alex Zami (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine and analyze the effect of career development and emotional intelligence on organizational citizenship behavior mediated by job satisfaction. The sample in this study used a saturated sample, where all the population was sampled, but employees as leaders and researchers were not included in the sample. The sample in this study amounted to 67 employees. The data collection technique in this study used a questionnaire method, with SEM-PLS statistical analysis. Data processing in this study using the SmartPLS 3.3.3 software program. The results of this study prove that career development directly has a positive and significant effect on organizational citizenship behavior. Furthermore, emotional intelligence has a positive and significant effect on organizational citizenship behavior. While job satisfaction has a positive and significant effect on organizational citizenship, and career development has a positive and significant effect on job satisfaction, while emotional intelligence has a positive and significant effect on job satisfaction, so that indirectly job satisfaction can mediate career development on organizational citizenship behavior. And indirectly, job satisfaction is able to mediate the influence of emotional intelligence on organizational citizenship behavior of employees.